2013
DOI: 10.1002/ffj.3137
|View full text |Cite
|
Sign up to set email alerts
|

The effect of wine closures on volatile sulfur and other compounds during post‐bottle ageing

Abstract: The effect of wine closures on volatile composition during post‐bottle ageing was investigated for Pinot Noir and Chardonnay wines. Natural cork, synthetic cork and screw caps with Saran–tin, Saranex and low density polyethylene (LDPE) liners were investigated over 3 years of storage. Dissolved O2 and SO2 as well as colour were monitored. Volatile sulfur compounds, esters, terpene alcohols, and C13‐norisoprenoids were quantified every 6 months over 3 years. The results showed that the LDPE screw cap gave the h… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
25
0
1

Year Published

2015
2015
2022
2022

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 33 publications
(31 citation statements)
references
References 25 publications
5
25
0
1
Order By: Relevance
“…Free SO 2 serves as an antioxidant, protecting wine from oxidation, and also can be an indicator of oxygen exposure and oxidative status in wine (Godden et al, 2001). The results demonstrated that both free and total SO 2 decreased significantly after the four years, storage, and the decreasing trend agreed with the OTR of each type of closure used to seal the bottles (He et al, 2013). Moreover, differences between conventional cork and synthetic closures were evident.…”
Section: Variation In Physical Properties Of the Closuressupporting
confidence: 61%
“…Free SO 2 serves as an antioxidant, protecting wine from oxidation, and also can be an indicator of oxygen exposure and oxidative status in wine (Godden et al, 2001). The results demonstrated that both free and total SO 2 decreased significantly after the four years, storage, and the decreasing trend agreed with the OTR of each type of closure used to seal the bottles (He et al, 2013). Moreover, differences between conventional cork and synthetic closures were evident.…”
Section: Variation In Physical Properties Of the Closuressupporting
confidence: 61%
“…Acetaldehyde, ethyl acetate, propanol, isobutyl alcohol, isoamyl acetate, and isoamyl alcohol were quantitated using the static headspace-GC-FID method described previously [ 46 ] due to their high concentrations in the sample. A Varian CP 3800 gas chromatograph equipped with a flame ionization detector (Varian, Inc., Palo Alto, CA, USA) was used.…”
Section: Methodsmentioning
confidence: 99%
“…Unlike β‐damascenone, β‐ionone was found to be stable during ageing (He et al . ). It appears to be more important to the aroma of red wine than of white wine, with the highest median concentration of 0.43 μg/L (69 analyses over seven publications) found for Pinot Noir (Table ), significantly higher than the odour threshold of 0.09 μg/L found in model wine (Table ).…”
Section: C13‐norisoprenoidsmentioning
confidence: 97%